1997
DOI: 10.1111/j.1439-0442.1997.tb01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and Postprandial Total Serum Bile Acid Concentration Following Acute Liver Damage in Dogs

Abstract: Summary The importance of preprandial and postprandial total bile acids were investigated in dogs with liver damage induced by carbon tetrachloride (CCl4) administration. Six healthy and mature dogs were used. After base‐line clinical and biochemical examinations, hepatocellular damage was induced by oral CCI4 administration. Determinations of plasma total protein (TP), albumin (Alb), total and direct bilirubin (TBil, DBil), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) along with histologic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The sensitivity of pre-and postprandial SBA to detect hepatic dysfunction is discussed controversially; some authors have shown little difference between both parameters for most disorders, 22 whereas others have demonstrated PP SBA to be superior. 2,23,24 A recent study found baseline SBA concentrations to have a sensitivity of 92.2% for the detection of a congenital PSS and 81% for acquired shunting. 9 In our study, none of the dogs with tracheal collapse had increased baseline SBA and 2 of 11 dogs with a PSS were missed with only a fasting SBA measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of pre-and postprandial SBA to detect hepatic dysfunction is discussed controversially; some authors have shown little difference between both parameters for most disorders, 22 whereas others have demonstrated PP SBA to be superior. 2,23,24 A recent study found baseline SBA concentrations to have a sensitivity of 92.2% for the detection of a congenital PSS and 81% for acquired shunting. 9 In our study, none of the dogs with tracheal collapse had increased baseline SBA and 2 of 11 dogs with a PSS were missed with only a fasting SBA measurement.…”
Section: Discussionmentioning
confidence: 99%